Current Pain and Headache Reports - Silberstein, Stephen; Newman, Lawrence C.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
This journal aims to review the most important, recently published clinical findings regarding the diagnosis, treatment, and management of pain and headache. By providing clear, insightful, balanced contributions by international experts, the journal intends to serve all those involved in the care and prevention of pain and headache. We accomplish this aim by appointing international authorities to serve as Section Editors in key subject areas, such as anesthetic techniques in pain management, cluster headache, neuropathic pain, and migraine. Section Editors, in turn, select topics for which leading experts contribute comprehensive review articles that emphasize new developments and recently published papers of major importance, highlighted by annotated reference lists. An international Editorial Board reviews the annual table of contents, suggests articles of special interest to their country/region, and ensures that topics are current and include emerging research. Commentaries from well-known figures in the field are also provided.
Keywords: Internal medicine; Pain medicine; Pain Medicine; Internal Medicine